Investment decision, legal certainty and its determinant factors: evidence from the Indonesia Stock Exchange - Benny Hutahayan; Mohamad Fadli; Satria Amiputra Amimakmur; Reka Dewantara (Cogent Business & Management, 2024)
In the context developing country, the relationship between legal certainty and investment decision is still an underexplored yet important context. This study investigates the effect of independent judicial system, legal culture, and the existence of government authority as the determinant factors that influence legal certainty and the influence of legal certainty on investment decisions in the context of companies listed on the Indonesian stock exchange. The research employs partial least squares structural equation modeling to analyze primary survey data gathered from 270 investors who are clients of Investment Management Companies in Indonesia. The results indicate that an independent judicial system, legal culture, and the existence of government authority significant and positively affecting legal certainty and legal certainty has a significant and positive effect on investment decisions. This findings have various intriguing implications and provide valuable insights into how policymakers can improve their municipal bond regulation strategy to have better legal certainty; which will encourage more investors to invest.
Keywords: 650; Indonesia stock exchange; legal certainty; investment decision; municipal bonds; structural equation modeling